2010
DOI: 10.1097/jes.0b013e3181d4957a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alterations in Total Hemoglobin Mass on V˙O2max

Abstract: Training and hypoxia-associated changes in maximal oxygen uptake are mediated by different blood adaptations. Training increases blood volume because of plasma and red cell volume expansion, resulting in increased cardiac output, whereas hypoxia increases only red cell volume, leading to increased hemoglobin concentration and oxygen transport capacity. Blood doping mimics the altitude effects, however, by far exceeding its magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
145
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(169 citation statements)
references
References 25 publications
16
145
4
4
Order By: Relevance
“…This is consistent with the higher VO 2peak relative to body mass. 27 Theoretically, this difference may be due to individual variations in training, heritage, and/or use of altitude training. The only differences in training we could identify were that the sprint skiers had higher volumes of speed training (P = .02) and strength training (P = .08).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the higher VO 2peak relative to body mass. 27 Theoretically, this difference may be due to individual variations in training, heritage, and/or use of altitude training. The only differences in training we could identify were that the sprint skiers had higher volumes of speed training (P = .02) and strength training (P = .08).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies centered on ‘sports anemia’ induced by endurance training. It is well documented in the literature that exercise training (mostly endurance training, but also strength training) can stimulate erythropoiesis and increase red cell mass as well as plasma volume, resulting in increased blood volume [for a review, see [4,5,6,7]]. This is evident in both women and men [8].…”
Section: Introductionmentioning
confidence: 97%
“…Finally, there is emerging recognition of considerable heterogeneity in the hematological response to exercise training, ranging from frank nonresponders to good responders, even in subjects with matched baseline characteristics. Erythropoiesis might be moderately influenced by exercise training and probably depends more on genetic predisposition [6]. …”
Section: Effects Of Exercise Training On the Erythrocytic Systemmentioning
confidence: 99%
“…It was stated that exercise increases total hemoglobin mass by stimulating erythropoiesis, which augments the amount of O2 that can be carried by blood. It was reported that an increase in tHb by 1 g achieved e.g., by administration of erythropoietin, increased VO2, max by ∼3ml/min (Schmidt and Prommer, 2010). Thus, augmented tHb and tEV in trained athletes proves that exercise stimulates erythropoiesis.…”
Section: Discussionmentioning
confidence: 97%